Data Privacy Management Strategy in IoT-Based Management Information Systems - Nazwa Retno; Muhammad Irwan Padli Nasution (Young Journal of Social Sciences and Humanities, 2025)
The development of the Internet of Things (IoT) has driven improvements in efficiency and effectiveness within management information systems (MIS) across various sectors, including industry, government, and education. However, increased connectivity and data exchange among devices introduce new risks related to data security and privacy. This article aims to identify strategies for managing data privacy in IoT-based management information systems through a conceptual approach and a review of recent literature. The findings indicate that effective strategies include implementing end-to-end encryption, multi-factor authentication, data anonymization, and strengthening data governance policies based on cybersecurity principles. In addition, integrating technical approaches with organizational policies is essential to ensure comprehensive privacy protection. This study contributes to the development of an adaptive data privacy management model in response to future IoT advances.